2021
DOI: 10.3390/pr9030556
|View full text |Cite
|
Sign up to set email alerts
|

Phase Distribution in the Tip Clearance of a Multiphase Pump at Multiple Operating Points and Its Effect on the Pressure Fluctuation Intensity

Abstract: Tip clearance has a great effect on the flow and pressure fluctuation characteristics in a multiphase pump, especially at multiple operating points. The phase distribution and pressure fluctuation in tip clearance in a multiphase pump are revealed using the CFD (computational fluid dynamics) technology and high-speed photography methods. In this paper, the phase distribution, the gas-liquid two-phase velocity slip, and the pressure fluctuation intensity are comprehensively analyzed. Results show with the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Xu et al [18] and Zhang et al [19] investigated the pressure pulsation characteristics of the multiphase pump and obtained the distribution and variation pattern of pressure fluctuations in the multiphase pump. Zhang et al [20] and Shi et al [21] studied the tip clearance of the multiphase pump and obtained the effect of tip clearance on energy characteristics, flow characteristics, and pressure fluctuations, respectively. Shi et al [22] and Li et al [23] investigated the effect of GVF on the energy conversion characteristics, pressure fluctuations, blade surface load, gas distribution, and external characteristics of a multiphase pump.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [18] and Zhang et al [19] investigated the pressure pulsation characteristics of the multiphase pump and obtained the distribution and variation pattern of pressure fluctuations in the multiphase pump. Zhang et al [20] and Shi et al [21] studied the tip clearance of the multiphase pump and obtained the effect of tip clearance on energy characteristics, flow characteristics, and pressure fluctuations, respectively. Shi et al [22] and Li et al [23] investigated the effect of GVF on the energy conversion characteristics, pressure fluctuations, blade surface load, gas distribution, and external characteristics of a multiphase pump.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing separation equipment is the traditional approach to separating oil and gas, which are then transported separately using a pump and compressor. As such, this process employs with complex piping systems and separation equipment, resulting in high investment costs [1,2]. In contrast, a two-phase transport platform eliminates part of the pipeline and separation equipment, saving 40% of infrastructure investment [3].…”
Section: Introductionmentioning
confidence: 99%
“…Liu Xiaobin et al [13] carried out the numerical simulations on the transient flow rate and dynamic characteristics of the multiphase pump and found that the flow rate conditions could be changed by the cavitation, to aggravate the unstable flow rate. Shi Guangtai et al [14] researched the phase distribution and pressure fluctuation in tip clearance in a multiphase pump. Wenwu Zhang et al [15] developed a Euler two-fluid model to analyze the phase interaction in the multiphase pump.…”
Section: Introductionmentioning
confidence: 99%